Las microalgas como indicadoras de contaminación del sitio El Donque en las aguas del Río Jubones en el cantón Pasaje - Maldonado Maldonado, Eliana S. (2005)
The Jubones river represents a very important hydric resource for our province being used for the watering of the banana plantations and short-cycle ones, as well as for the population which use its water for the industries and human consumption. However, its basin is being modified due to the presence of polluting discharges in it effluents.